Evaluation of Bone Heating, Drill Deformation, and Drill Roughness After Implant Osteotomy: Guided Surgery and Classic Drilling Procedure - dos Santos, Pâmela Letícia; Queiroz, Thallita Pereira; Margonar, Rogério; de Souza Carvalho, Abrahão Cavalcante Gomes [UNESP]; Betoni, Walter; Rezende, Regis Rocha Rodrigues; dos Santos, Paulo Henrique [UNESP]; Garcia, Idelmo Rangel [UNESP] (Quintessence Publishing, 2014)
Purpose: This study evaluated and compared bone heating, drill deformation, and drill roughness after several implant osteotomies in the guided surgery technique and the classic drilling procedure. Materials and Methods: The tibias of 20 rabbits were used. The animals were divided into a guided surgery group (GG) and a control group (CG); subgroups were then designated (G0, G1, G2, G3, and G4, corresponding to drills used 0, 10, 20, 30 and 40 times, respectively). Each animal received 10 sequential osteotomies (5 in each tibia) with each technique. Thermal changes were quantified, drill roughness was measured, and the drills were subjected to scanning electron microscopy. Results: Bone temperature generated by drilling was significantly higher in the GG than in the CG. Drill deformation in the GG and CG increased with drill use, and in the CG a significant difference between G0 and groups G3 and G4 was observed. In the GG, a significant difference between G0 and all other groups was found. For GG versus CG, a significant difference was found in the 40th osteotomy. Drill roughness in both groups was progressive in accordance with increased use, but there was no statistically significant difference between subgroups or between GG and CG overall. Conclusion: During preparation of implant osteotomies, the guided surgery technique generated a higher bone temperature and deformed drills more than the classic drilling procedure. The increase in tissue temperature was directly proportional to the number of times drills were used, but neither technique generated critical necrosisinducing temperatures. Drill deformation was directly proportional to the number of times the drills were used. The roughness of the drills was directly proportional to the number of reuses in both groups but tended to be higher in the GG group. Int J Oral Maxillofac Implants 2014;29:51-58. doi: 10.11607/jomi.2919
Keywords: bone overheating; dental implants; osteotomy